Determinants of Credit Growth For MSME Financing in Bank DKI in Jakarta Province - Aristo Purboadji; Hakim, Dedi Budiman; Siregar, Hermanto; Sembel, Roy (School of Business, Bogor Agricultural University (SB-IPB), 2022)
This study aims to analyze the determinants that affect the growth of MSME credit at Bank DKI in DKI Jakarta Province. The independent variables used consist of ROA, NPL, CAR, Spread, Marketing Expense, GDP and Inflation. The data used is quarterly secondary data for the period January 2014 – December 2018. The analysis is carried out as a whole and economic segments (10 sectors) so as to form 11 regressions (sectors) using the EGLS panel model fixed effect model (Cross–Section SUR). The results of this study indicate that Sector 1 (One) is affected by ROA, NPL, and GDP; Sector 2 (Two) is affected by ROA, NPL, CAR, and Inflation; Sector 3 (Three) is affected by NPL, CAR and Inflation; Sector 4 (Four) is affected by NPL, CAR and inflation; Sector 5 (Five) influenced by ROA, NPL, CAR, PEX and GDP; Sector 6 (Six) affected by CAR, PEX, Spread, and GDP; Sector 7 (Seven) affected by ROA, NPL and Spread; Sector 8 (Eight) affected by ROA, NPL, CAR, PEX, Spread, GDP and Inflation; Sector 9 (Nine) affected by ROA; Sector 10 (Ten) affected by ROA, NPL, Spread and GDP; Sector 11 (Eleven) is affected by ROA, NPL, CAR, GDP and Inflation. The results of the study indicate that banks must prioritize certain financial ratios in each MSME sector to grow their credit growth. Keywords: credit growth, MSMEs, macro factors, micro factors, regional development bank